An ethylene biosynthesis enzyme controls quantitative variation in maize ear length and kernel yield - Qiang Ning; Yinan Jian; Yanfang Du; Yunfu Li; Xiaomeng Shen; Haitao Jia; Ran Zhao; Jimin Zhan; Fang Yang; David Jackson; Lei Liu; Zuxin Zhang (Nature Communications, 2021)
Considerable genetic variation exists in maize ear size and kernel number. Here the authors show that variation in a gene encoding an ethylene biosynthetic enzyme impacts ear length, flower fertility and kernel yield suggesting an important role for ethylene signaling during inflorescence development.